Maternal sensitivity at the age of 8 months associates with local connectivity of the medial prefrontal cortex in children at 5 years of age - Copeland Anni; Korja Riikka; Nolvi Saara; Rajasilta Olli; Pulli Elmo P; Kumpulainen Venla; Silver Eero; Saukko Ekaterina; Hakanen Hetti; Holmberg Eeva; Kataja Eeva-Leena; Häkkinen Suvi; et al. (Frontiers Media SA, 2022)
The quality of mother-child interaction, especially maternal sensitivity in caregiving behavior, plays an important role in a child's later socioemotional development. Numerous studies have indicated associations between poor mother-child interaction and offspring brain structure and function, but more knowledge on how variation in the characteristics of early caregiving is associated with children's brain structure and function is needed. We investigated whether maternal sensitivity at 8 or 30 months is associated with functional connectivity in a child's brain at 5 years of age based on the FinnBrain Birth Cohort Study (17 and 39 mother-child dyads at 8 and 30 months, respectively, with an overlap of 13 dyads). Maternal sensitivity was assessed during a free play interaction using the Emotional Availability Scales at 8 and 30 months of the children's age. Task-free functional magnetic resonance imaging (fMRI) was acquired at the age of 5 years in 7-min scans while watching the Inscapes movie. Regional homogeneity (ReHo) maps were created from the fMRI data, and multiple regression analysis was performed to assess the relation between maternal sensitivity and ReHo. Maternal sensitivity at the age of 8 months was positively associated with children's ReHo values within the medial prefrontal cortex. Distal connectivity of this region showed no significant association with maternal sensitivity in a seed-based connectivity analysis. No associations were found between maternal sensitivity during toddlerhood and brain functional connectivity. Together, these results suggest that maternal sensitivity, especially in infancy, may influence offspring brain functional connectivity. However, studies with larger sample sizes are warranted.